giúp mj câu 3A a,b ;4A b và 6A a,b với mj cảm ơn trước

Question

giúp mj câu 3A a,b ;4A b và 6A a,b với
mj cảm ơn trước
giup-mj-cau-3a-a-b-4a-b-va-6a-a-b-voi-mj-cam-on-truoc

in progress 0
King 2 years 2020-10-18T11:39:10+00:00 1 Answers 84 views 0

Answers ( )

    0
    2020-10-18T11:41:02+00:00

    Đáp án:

     6A.b. 1

    Giải thích các bước giải:

    \(\begin{array}{l}
    3A.a.\sqrt 2 .\sqrt 2  + 5\sqrt 2 .\sqrt 2  – 2\sqrt 6 .\sqrt 6 \\
     = 2 + 10 – 12 = 0\\
    b.\sqrt {6 + 2\sqrt 5 }  = \sqrt {5 + 2.\sqrt 5 .1 + 1} \\
     = \sqrt {{{\left( {\sqrt 5  + 1} \right)}^2}}  = \sqrt 5  + 1\\
    4A.b.\dfrac{{\sqrt {36 – 12\sqrt 5 } }}{{\sqrt 6 }} = \dfrac{{\sqrt {6\left( {6 – 2\sqrt 5 } \right)} }}{{\sqrt 6 }}\\
     = \sqrt {6 – 2\sqrt 5 }  = \sqrt {5 – 2.\sqrt 5 .1 + 1} \\
     = \sqrt {{{\left( {\sqrt 5  – 1} \right)}^2}}  = \sqrt 5  – 1\\
    6A.a.\sqrt {\dfrac{{ – 2t.\left( { – 3t} \right)}}{{3.8}}}  = \sqrt {\dfrac{{6{t^2}}}{{24}}} \\
     = \left| t \right|.\sqrt {\dfrac{1}{4}} \\
     = \dfrac{{ – t}}{2}\left( {Do:t \le 0} \right)\\
    b.\sqrt {x – \sqrt {{x^2} – 1} } .\sqrt {x + \sqrt {{x^2} – 1} } \\
     = \sqrt {{x^2} – {{\left( {\sqrt {{x^2} – 1} } \right)}^2}} \\
     = \sqrt {{x^2} – {x^2} + 1}  = 1
    \end{array}\)

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )